Parenteral Antibiotics Reduce Bifidobacteria Colonization and Diversity in Neonates - Séamus Hussey; Rebecca Wall; Emma Gruffman; Lisa O'Sullivan; C. Anthony Ryan; Brendan Murphy; Gerald Fitzgerald; Catherine Stanton; R. Paul Ross (International Journal of Microbiology)
We investigated the impact of parenteral antibiotic treatment in the early neonatal period on the evolution of bifidobacteria in the newborn. Nine babies treated with intravenous ampicillin/gentamicin in the first week of life and nine controls (no antibiotic treatment) were studied. Denaturing gradient gel electrophoresis was used to investigate the composition of Bifidobacterium in stool samples taken at four and eight weeks. Bifidobacteria were detected in all control infants at both four and eight weeks, while only six of nine antibiotic-treated infants had detectable bifidobacteria at four weeks and eight of nine at eight weeks. Moreover, stool samples of controls showed greater diversity of Bifidobacterium spp. compared with antibiotic-treated infants. In conclusion, short-term parenteral antibiotic treatment of neonates causes a disturbance in the expected colonization pattern of bifidobacteria in the first months of life. Further studies are required to probiotic determine if supplementation is necessary in this patient group.